TYPES OF REFRACTIVE ERRORS IN POPULATIONS AGED 20-40 YEARS ATTENDED DUHOK EYE HOSPITAL - MASOUD, NOUR MOAFIQ (Journal of Duhok University, 2023)
Background One of the most common eye problemsare refractive errors. They occurwhen the eye cannot clearly focus the images. Which result in a blurred vision,sometimesthey are so severe that they causevisual impairment. Aim The study is to resolute refractive error types in 20-40 years-old population. Methodology 300 patients aged from20 to 40 years old who attend Duhok Eye Hospital;Duhok governorate;Kurdistan including from 1st April 2022 to 1st October 2022 are included in thiscross-sectional study. Examinations of visual acuity,anterior and posterior segments were done for theparticipants and were categorized into myopia, hyperopia, and astigmatism. Results Myopia with astigmatism were most common type (46.50%),followed by astigmatism (26.8%) for the right eye,Myopia with astigmatism were most common type (48.3%),followed by astigmatism(26.7%) for the left eye;(59.9%) were females while (40.1%) were males;22% of patients were newly diagnosed while 78%were following up visits. Conclusions Decrease visual acuity due to refractive errors in young age group people has a very important impact on their lives and productivity,and also great burden on their financial status;early diagnosis and correction must be done to avoid such effects and impacts